(untitled) (LACCEI, 2024)
This article aims to determine how the VAT deduction system affects the liquidity of TRANSPORTES 95-430 EIRL, Trujillo-2020-2021.research is quantitative, non-experimental design and descriptive-correlational level, with a population focused on TRANSPORTES 95-430 EIRL, Trujillo-2020-2021. In addition, documentary analysis was used as a data collection technique, it was found that liquidity was significantly affected in the company due to the non-compliance of the deposit in the deduction account of the bank of the nation by the purchaser of the services provided, generating a decrease in the liquidity of the company and affecting it for the cancellation of all the taxes corresponding to that period and reducing the investment of working capital. It is concluded that the application of the VAT deduction system reduces the company’s liquidity, which reduces its economic and financial capacity to meet its short-term debts, as well as impeding the expansion of its business.